Development and comparison of regression models for the uptake of metals into various field crops - Novotná, Markéta; Mikeš, Ondřej; Komprdová, Klára (Environmental pollution (1987), 2015)
Field crops represent one of the highest contributions to dietary metal exposure. The aim of this study was to develop specific regression models for the uptake of metals into various field crops and to compare the usability of other available models. We analysed samples of potato, hop, maize, barley, wheat, rape seed, and grass from 66 agricultural sites. The influence of measured soil concentrations and soil factors (pH, organic carbon, content of silt and clay) on the plant concentrations of Cd, Cr, Cu, Mo, Ni, Pb and Zn was evaluated. Bioconcentration factors (BCF) and plant-specific metal models (PSMM) developed from multivariate regressions were calculated. The explained variability of the models was from 19 to 64% and correlations between measured and predicted concentrations were between 0.43 and 0.90. The developed hop and rapeseed models are new in this field. Available models from literature showed inaccurate results, except for Cd; the modelling efficiency was mostly around zero. The use of interaction terms between parameters can significantly improve plant-specific models.
Keywords: Zea mays; Metals, Heavy; Multivariate Analysis; Environmental Monitoring; Soil Pollutants; látky znečišťující půdu; půda; kukuřice setá; pšenice; Regression Analysis; monitorování životního prostředí; Crops, Agricultural; těžké kovy; multivariační analýza; teoretické modely; kontaminace potravin; Food Contamination; Czech Republic; Brassica rapa; Triticum; Soil; Models, Theoretical; Česká republika; regresní analýza; zemědělské plodiny